Analysis study and SDR implementation of GoF‐based spectrum sensing for cognitive radio. Issue 5 (1st March 2020) - Teguig, Djamal; Azzaz, Mohamed Salah; Sadoudi, Said
Abstract : Cognitive radio (CR) technology is getting extensive attention to eliminate the problem of spectrum scarcity. This technology is based on Software Defined Radio (SDR) and some integrated intelligent functions such as spectrum sensing. This function is one of the crucial elements and its hardware implementation is important for the practical realization of the CR. This paper presents experimental results of the hardware implementation of the Goodness of Fit (GoF) based sensing for CR. Universal Software Radio Peripheral platform (USRP) is used for the experiments conducted. The choice of GoF based sensing for detecting spectrum holes is motivated by the advantage of requiring fewer samples to achieve the same sensing performance compared to Energy Detector (ED). Besides, the analytical expressions for the theoretical detection performance are derived. Computer simulations are carried out to evaluate the impact of fading channels on GoF based sensing. Numerical results confirm that the proposed GoF based sensing method outperform ED under fading channels. Furthermore, theoretical results of GoF based spectrum sensing are validated experimentally taking into account some parameters such as sample rate and sensing time. Finally, several scenarios of wideband GoF based sensing are considered to demonstrate the strengths of the considered method.